2011
DOI: 10.4194/trjfas.2011.0112
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Commercial culture of carnivorous fish demands the reduction of environmental impact of feeds; that requires minimal use of dietary animal protein. This study investigated the digestibility of diets formulated exclusively out of plant protein, added rendered ingredients and feed attractants, by the carnivore European sea bass, Dicentrarchus labrax. Juvenile European sea bass (14.0±1.0 cm) conditioned to accept artificial dry feed were stocked in polypropylene cages and fed ad libitum in three daily meals, seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Although dietary fiber cannot be directly utilized by fish, it can still have varying degrees of physiological effects on fish ( 1 ). Some studies have shown that low dietary fiber diets benefit fish growth, while high dietary fiber diets inhibit fish growth ( 22 , 29 , 30 ). Therefore, NRC ( 31 ) recommends that fish dietary fiber levels should not exceed 10%.…”
Section: Discussionmentioning
confidence: 99%
“…Although dietary fiber cannot be directly utilized by fish, it can still have varying degrees of physiological effects on fish ( 1 ). Some studies have shown that low dietary fiber diets benefit fish growth, while high dietary fiber diets inhibit fish growth ( 22 , 29 , 30 ). Therefore, NRC ( 31 ) recommends that fish dietary fiber levels should not exceed 10%.…”
Section: Discussionmentioning
confidence: 99%
“…The high fiber content in frass is not digestible for carnivorous fish such as pompano that have short intestines, meaning it has little nutritional value for these species. Previous work that evaluated the effects of dietary fiber on fish growth suggested that the supplementation should be restricted to less than 7% for European sea bass [ 40 ] and 8.5% for largemouth bass [ 41 ]. Moreover, the National Research Council [ 42 ] suggested that the dietary fiber level of the fish diet should not exceed 10%.…”
Section: Resultsmentioning
confidence: 99%
“…Many researchers have studied the effects of substituting FM with plant-based proteins [23][24][25][26][27][28]. Completely replacing animal proteins with plant proteins has generally not been successful due to concerns about antinutrients, changes in amino-acid absorption, potential micronutrient deficiencies, and immune suppression [29][30][31].…”
Section: Introductionmentioning
confidence: 99%